MSME Assistance Through Instagram Social Media Management Activities in Entrepreneurship - Sevira Dwi Shabrina; Ainur Rochmaniah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Community service activities are an effort to help the community in certain activities without expecting any form of reward. This community service also serves as assistance to MSME business owners 24sweetness and Anskitchen regarding the management of Instagram social media so that they understand more about digital marketing. The marketing used by these MSMEs is still relatively small and unfamiliar with technology. So, with the assistance of MSMEs through Instagram social media management, it can increase sales at 24sweetness and Anskitchen and can attract consumer attention. The implementation method in this service begins with interviews, observations and assistance in content writing. Planned content creation starts from product photos/videos, sorting and editing sessions, uploading Instagram feeds and copywriting on caption creation. The results of this service showed that consumer interest increased, especially on the Anskitchen and 24sweetness Instagram platforms. At the same time, MSME owners also understand the marketing system, including using an attractive and effective Instagram platform to create the content needed for marketing.